2006
DOI: 10.1002/ca.20344
|View full text |Cite
|
Sign up to set email alerts
|

Integrating professionalism in early medical education: The theory and application of reflective practice in the anatomy curriculum

Abstract: Renewed emphases on teaching professionalism require physicians to develop the ability to critically reflect upon their own decisions. Innovative programs that address teaching professionalism within medical curricula have been implemented in almost all medical schools. The foundation for many of these programs is "reflection," which is regarded as a core skill in professional competence. In order to achieve the desired outcomes and meet the demands of a required curriculum, an understanding of educational con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 19 publications
(19 reference statements)
3
166
0
1
Order By: Relevance
“…Another explanation may be that the process of discovering and presenting anatomical structures parallels diagnostic reasoning, the underpinnings of which are built on the tenants of observation, interpretation, and differential identification (Rizzolo and Stewart, 2006). While there is literature supporting the role for dissection in developing professional skills (Pawlina and Lachman, 2004;Escobar-Poni and Poni, 2006;Lachman and Pawlina, 2006), there remains a dearth of studies exploring the role of dissection alternatives in imparting such skills. Is the acquisition of professional skills inherent solely in donor dissection activities or is it perhaps integrated more holistically in the broader fabric of a well-rounded anatomy education curriculum?…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that the process of discovering and presenting anatomical structures parallels diagnostic reasoning, the underpinnings of which are built on the tenants of observation, interpretation, and differential identification (Rizzolo and Stewart, 2006). While there is literature supporting the role for dissection in developing professional skills (Pawlina and Lachman, 2004;Escobar-Poni and Poni, 2006;Lachman and Pawlina, 2006), there remains a dearth of studies exploring the role of dissection alternatives in imparting such skills. Is the acquisition of professional skills inherent solely in donor dissection activities or is it perhaps integrated more holistically in the broader fabric of a well-rounded anatomy education curriculum?…”
Section: Discussionmentioning
confidence: 99%
“…In the context of future curriculum planning, it might be necessary to provide not only sufficient anatomical know-how (Bergman et al, 2008;Fitzgerald et al, 2008) but also professionalism training. The aforementioned professional competencies are qualities our students hope to gain during their studies (Skiles, 2005), and we as faculty are responsible for making these competencies part of our curricula (Lachman and Pawlina, 2006;Slotnick and Hilton, 2006). Some medical schools, including the Ulm University, have already started to implement these qualities in their graduate profile (Mueller et al, 2008).…”
Section: Professional Competenciesmentioning
confidence: 99%
“…In one study about medico-legal autopsy teaching, autopsies were found to carry a considerable hidden curriculum concerning attitudes of respect, empathy, and compassion (McNamee et al, 2009). Laboratories promote reflection (Lachman and Pawlina, 2006) and develop students' humanity.…”
Section: Ambivalent Emotionmentioning
confidence: 99%